Modeling Concepts for Choice Navigation of Mass Customized Solutions - Heiskala, Mikko; Tiihonen, Juha; Sievänen, Matti; Paloheimo, Kaija-Stiina (International Journal of Industrial Engineering and Management, 2010)
Customers want individualized solutions regardless of whether the solutions comprise products, services, or any combination of them. Choice navigation support is a key capability for a company offering such mass customized solutions. We seek to identify modelling concepts for supporting choice navigation. Our findings draw from our case experiences in seven companies and scientific literature. We propose concepts such as bundles, explicit customer needs and characteristics affecting determination of the optimal solution, and high-level service co-creation process. These concepts partly extend physical product configuration conceptual models, providing a good basis for improving choice navigation support for solutions. Article history: Received (25.07.2010); Revised (27.09.2010); Accepted (03.10.2010)